The Relationship Between Knowledge of Postpartum Mothers About Perineal Wound Treatment With Perineal Wound Healing - Yosi Yusrotul Khasanah; Agi Yulia Ria Dini; Wahyuni Ade Saputri (Indonesian Health Journal, 2022)
Postpartum infection still plays a role as the leading cause of maternal death, especially in developing countries such as Indonesia, this problem occurs as a result of midwifery services that are still far from perfect. As a result of improper perineal care, the perineum is affected by lochia and moist conditions that will significantly support the proliferation of bacteria that can cause infection in the perineum. Infection not only inhibits the wound healing process but can also cause damage to the supporting cell tissue, increasing the size of the wound itself, both in length and depth of the wound. Perineal wound care aims to prevent infection, increase comfort, and accelerate healing. Those who have episiotomy or laceration wounds need to have sufficient knowledge about perineal wound care because these factors significantly affect the healing process of the perineal wound. The knowledge of postpartum mothers about poor perineal wound care can be a factor that causes germs and bacteria to appear. This study aimed to determine the relationship between postpartum mothers' knowledge of perineal wound care and perineal wound healing. This research uses a descriptive correlation with a quantitative approach to the point of sampling technique using total sampling with 16 respondents. How to collect data using a questionnaire. Data analysis used the chi-square test to test the relationship between two variables. There is a relationship between postpartum mothers' knowledge about perineal wound care and perineal wound healing, with a significant value of 0.005 (p-value <0.05). There is a relationship between postpartum mothers' knowledge of perineal wound care and perineal wound healing